2015
DOI: 10.1186/s12879-015-0878-z
|View full text |Cite
|
Sign up to set email alerts
|

Nasal mucosal microRNA expression in children with respiratory syncytial virus infection

Abstract: BackgroundRespiratory syncytial virus (RSV) infection is a common cause of pediatric hospitalization. microRNA, key regulators of the immune system, have not previously been investigated in respiratory specimens during viral infection. We investigated microRNA expression in the nasal mucosa of 42 RSV-positive infants, also comparing microRNA expression between disease severity subgroups.MethodsNasal mucosa cytology specimens were collected from RSV-positive infants and healthy controls. 32 microRNA were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 53 publications
4
63
0
Order By: Relevance
“…32 Moreover, Ninio-Many et al 33 indicated miR-125a modulates molecular pathway of motility and migration via Fyn expression in prostate cancer cells. In addition, miR-125a has been associated with many diseases, including autoimmune diseases, 20 cardiovascular diseases, 34, 35 microbial infection 36, 37 and hematological malignancies. 20, 30 Recent data indicate that miR-125a upregulation sensitized paclitaxel-resistant colon cancer cells to paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, Ninio-Many et al 33 indicated miR-125a modulates molecular pathway of motility and migration via Fyn expression in prostate cancer cells. In addition, miR-125a has been associated with many diseases, including autoimmune diseases, 20 cardiovascular diseases, 34, 35 microbial infection 36, 37 and hematological malignancies. 20, 30 Recent data indicate that miR-125a upregulation sensitized paclitaxel-resistant colon cancer cells to paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…In these CRC experiments, we found that dsRNA induced the expression of MYD88, MDA‐5, RIG‐I, and TLR‐3 (Figure A), which are classical innate immune signaling responses observed in AEC . The induction of these genes was coupled with downstream expression of STAT1 and the induction of AEC antiviral chemokines such as CXCL11, CXCL10, and CCL5 (Figure B), as well as interferon (IFN)‐stimulated genes such as IFIT1, IFI44, OAS2, and MX1 (Figure A) . Notably, IFN regulatory transcription factor 7 (IRF‐7), which regulates transcriptional activation of virus‐inducible IFN genes in AEC, was also overexpressed.…”
Section: Resultsmentioning
confidence: 98%
“…Of the miRNAs found to be expressed in TIGKs, miR-210 has been earlier documented in gastric epithelium (31) as well as in human skin keratinocytes (32); members of the miR-200 family (to which miR-141 belongs) are known to be involved in epithelial to mesenchymal transition during tumorigenesis (33,34). miR-155 was found to be expressed in nasal epithelium cytology brushings in children with respiratory syncytial virus infection (35), while miR-126 was found in normal basal and luminal mammary epithelium (36). We are unaware of any literature describing epithelial expression of miR-1246.…”
Section: Resultsmentioning
confidence: 99%